A Place for Immigrants in the Ghetto: The Rise and Fall of the NaunynRitze Youth Centre. Issue 4 (November 2019) - Güney, Serhat; Kabaş, Bülent; Çömlekçi, Fatih
In this work, we attempt to examine the role of strategies like arts sponsorship and culturalism in the solution of immigrant youth issues around a specific immigrant place. This is a case study that focuses on the NaunynRitze Youth Centre in Berlin-Kreuzberg, which was presented as a successful example by policy makers and the public in the 1990s when the footsteps of the crisis of multiculturalism had begun to be heard in Germany. Our research shows that the social engineering strategies shaped around a multikulti production base are not permanent or sustainable as long as these institutions are also given the responsibility of eliminating the cycle of crime and violence in addition to promote individual artistic development and subcultural entities. As long as political figures and the public opinion continue to generally see the immigrant youth as a danger to the secure and untarnished development of society, it does not appear possible for the multiculturalism and the immigrant youth work system to develop.